Brand Image and What Prices Can Determine the Decision Process of Buying Erigo Products in Bandung City - Henry Meytra Taufik; Aziza Nabila Amalia (Budapest International Research and Critics University, 2022)
The purpose of this study was to determine whether brand image and price can determine the purchasing decision process of Erigo products. The research method used is descriptive and verification research methods. The data collection technique is through a questionnaire with data analysis using validity, reliability, classical assumption test, multiple linear regression analysis, hypothesis testing and coefficient of determination. The results of the calculation of the coefficient of determination show that the percentage of the influence of Brand Image and Price on Purchase Decisions has a positive effect on Erigo products, and the results of hypothesis testing indicate that brand image and price have a significant effect on the purchasing decision process of Erigo Products.